Integration of Local Wisdom of Malang Regency in Language Conservation Strategy: An Ethnolinguistic Model for Cultural Sustainability - M. Isnaini (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to develop an ethnolinguistic model to integrate local wisdom of Malang Regency into language conservation strategies as an effort to ensure cultural sustainability in the era of modernization. The challenges of globalization threaten the sustainability of regional languages, especially among the younger generation, so a comprehensive approach that integrates local wisdom into conservation strategies is needed. The study used a systematic literature review method of 45 Indonesian ethnolinguistic publications for the period 2014-2025 which were analyzed thematically covering ethnolinguistic concepts, manifestations of local wisdom, conservation strategies, and challenges of modernization. The results show that local wisdom is manifested in five main forms: ritual terminology, toponymy, pantun and proverbs, traditional economic practices, and ecological knowledge. Ethnolinguistics provides a comprehensive theoretical framework for understanding the intrinsic relationship between language and culture, but most research is still descriptive with limitations in the development of practical intervention models. The proposed ethnolinguistic model is built on five pillars: participatory documentation, contextual revitalization, intergenerational transmission, adaptive technology, and institutional sustainability. This model makes a theoretical contribution by expanding ethnolinguistics from a descriptive analytical tool to a practical intervention paradigm, and also provides a practical roadmap for developing contextual and sustainable language conservation policies. The research confirms that the preservation of regional languages cannot be separated from the preservation of local wisdom as a whole as an investment in the sustainability of the nation's cultural identity.